Monthly Intramuscular Neridronate for the Treatment of Postmenopausal Osteoporosis: Results of a 6-Year Prospective Italian Study. (6th February 2019) - Guiducci, L.; Vassalle, C.; Parchi, P.; Maffei, S.
Abstract : Purpose . Oral bisphosphonates (BPs) are the most commonly used medications for osteoporosis (OP), but their poor gastrointestinal (GI) absorption and tolerance hamper compliance. Intramuscular (IM) neridronate (NE), an amino-BP, is an easy-to-administer, effective, and safe alternative to oral BPs. We assessed the 6-year effects of monthly IM NE on bone mineral density (BMD) and bone turnover biomarkers (BMs) in postmenopausal OP. Methods . This single-center, prospective study enrolled postmenopausal osteoporotic outpatients with gastric intolerance to BPs (based on Tuscany Region's law GRT n. 836 20/10/2008). They received 25 mg IM NE once a month (with vitamin D and calcium if necessary) for 6 years. BMD was evaluated at lumbar spine (L1-L4), femoral neck (FN), and total femur (TF) at baseline (BL) and every 12 months afterwards. At BL, month 3, and every 12 months after BL, total and ionized calcium, vitamin D, parathyroid hormone 1-84, bone alkaline phosphatase (BALP), osteocalcin, and N- and C-terminal telopeptides were assayed. Results . Overall, 60 women (mean age:62.3 ± 7.5 years) received monthly IM NE for 6 years, with vitamin D and calcium supplementation in 81.3% of cases. Compared to BL, BMD increased significantly already after 1 year at all sites (4.5 ± 0.9 % for L1-L4, 4.5 ± 0.8 % for TF, and2.1 ± 0.6 % for FN, P ≤ 0.05 ), and the changes were maintained over time, whereas FN further improved up to year 3 and remained stable afterwards (P ≤ 0.05 ). All BMs, except for total calcium and BALP, progressively decreased over time (P ≤ 0.05 ). No fractures and significant adverse events were reported. Conclusion. The monthly administration of IM NE represents a manageable and effective option, in terms of BMD and bone BM improvement, for the long-term treatment of postmenopausal OP women with gastric intolerance to BPs. This trial is registered with ClinicalTrials.gov Identifier:NCT03699150 .